2009
DOI: 10.3168/jds.2008-1903
|View full text |Cite
|
Sign up to set email alerts
|

Crushed sunflower, flax, or canola seeds in lactating dairy cow diets: Effects on methane production, rumen fermentation, and milk production

Abstract: The objective of this study was to investigate the potential of reducing enteric methane production from dairy cows by incorporating into the diet various sources of long-chain FA varying in their degree of saturation and ruminal availability. The experiment was conducted as a crossover design with 16 lactating dairy cows maintained in 2 groups and fed 4 dietary treatments in four 28-d periods. Eight ruminally cannulated primiparous cows (96 +/- 18 d in milk) were assigned to group 1 and 8 multiparous cows (13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
198
8
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(250 citation statements)
references
References 29 publications
32
198
8
4
Order By: Relevance
“…The effectiveness of linseed in reducing ruminal methanogenesis in this experiment with grazing animals is consistent with that reported in the literature on confined animals (EugĂšne et al, 2008;Beauchemin, et al, 2009;Martin et al, 2010), with the results reported in this work. According to Morgavi et al (2010), the mitigation of rumen methanogenesis can be achieved by reducing the H 2 supply to the methanogenics obtained from favoring the production of propionate and the methanogenic archaea and protozoa (H 2 producers) .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The effectiveness of linseed in reducing ruminal methanogenesis in this experiment with grazing animals is consistent with that reported in the literature on confined animals (EugĂšne et al, 2008;Beauchemin, et al, 2009;Martin et al, 2010), with the results reported in this work. According to Morgavi et al (2010), the mitigation of rumen methanogenesis can be achieved by reducing the H 2 supply to the methanogenics obtained from favoring the production of propionate and the methanogenic archaea and protozoa (H 2 producers) .…”
Section: Discussionsupporting
confidence: 82%
“…This reduction was similar to the 33% observed by Chung et al (2011) and higher than the 27% observed by Martin et al (2008) and the 18% observed by Beauchemin et al (2009), using linseed as a lipid source and corn silage as forage. All diets with lipid sources contained, on average, 34 g of additional lipid per kilogram of DM and the reduction of CH 4 emissions in animals supplemented with linseed oil was of 4 g per kilogram of DM intake.…”
Section: Discussionsupporting
confidence: 62%
“…On the contrary, sunflower seed (rich in linoleic acid) had a similar depressive effect as coconut oil on CH 4 production, and this effect was higher than rapeseed (rich in oleic acid), and especially than linseed (rich in linolenic acid), in vitro (MachmĂŒ ller et al, 1998) and in vivo (MachmĂŒ ller et al, 2000). Recently, Beauchemin et al (2009) reported that CH 4 production in dairy cows was more affected by linseed and rapeseed (217% on average) than by sunflower seeds (210%). Other FA present in fish oil or in some algae also have a In vivo trials clearly show that the effect of lipids on methanogenesis is proportional to their level of supply (Figure 2).…”
Section: Mitigation Through Feedingmentioning
confidence: 99%
“…Numerous studies have demonstrated that the use of specific forage species, forage conservation methods and dietary lipid supplements can be used to alter milk fat composition in ruminants (Dewhurst et al, 2006;Chilliard et al, 2007;Glasser et al, 2008a). Furthermore, plant oils and oilseeds in the diet also decrease methanogenesis in ruminants (MachmĂŒ ller et al, 2003;Martin et al, 2008;Beauchemin et al, 2009). Due to the interrelationship between diet composition, rumen metabolism and mammary lipogenesis, on-farm feeding regimens for decreasing greenhouse gas emissions or altering milk fatty acid composition can also be expected to influence milk fat content ) depending on diet composition and ruminant species.…”
Section: Introductionmentioning
confidence: 99%